2018
DOI: 10.3390/ijms19082392
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized Tissue for Muscle Regeneration

Abstract: Several acquired or congenital pathological conditions can affect skeletal muscle leading to volumetric muscle loss (VML), i.e., an irreversible loss of muscle mass and function. Decellularized tissues are natural scaffolds derived from tissues or organs, in which the cellular and nuclear contents are eliminated, but the tridimensional (3D) structure and composition of the extracellular matrix (ECM) are preserved. Such scaffolds retain biological activity, are biocompatible and do not show immune rejection upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 62 publications
0
56
0
Order By: Relevance
“…These surgical procedures, however, are technically difficult, have limited success, and result in donor site morbidity (Turner & Badylak, ). Due to these limitations, experimental approaches in the form of tissue engineered xenotransplants made from decellularized tissue (Urciuolo & De Coppi, ) and cell therapy (Qazi et al, ) are currently being explored. There is an urgent need for new therapies that can restore functional muscle tissue following traumatic injury.…”
Section: Introductionmentioning
confidence: 99%
“…These surgical procedures, however, are technically difficult, have limited success, and result in donor site morbidity (Turner & Badylak, ). Due to these limitations, experimental approaches in the form of tissue engineered xenotransplants made from decellularized tissue (Urciuolo & De Coppi, ) and cell therapy (Qazi et al, ) are currently being explored. There is an urgent need for new therapies that can restore functional muscle tissue following traumatic injury.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we have demonstrated that the main components of the extracellular matrix are overall conserved both structurally and on their composition with some variations. Specifically, collagen quantification showed an increase in the relative content, which is due to the fact that, by removing cells, the ratio between the different ECM components change in respect to the overall tissue weight, in particular for collagen which is the most abundant one as previously described for other tissues [ 28 ]. Beside collagen, elastin ratio was maintained, of note, preservation of collagen and elastin is an important feature to maintain the biomechanical response of the tissue once transplanted.…”
Section: Discussionmentioning
confidence: 93%
“…Biomaterials are pivotal, as their interaction with the seeded cells will determine the final result of the tissue-engineered construct. For this aim, dealing with biologically derived materials seems to be a reasonable option, if the most relevant biochemical cues are preserved [ 9 , 15 , 16 ].…”
Section: Moving Towards Biomimetic Engineered Muscular Constructsmentioning
confidence: 99%
“…Dealing with a comprehensive tissue engineering protocol underlines, therefore, the necessity of developing a biomimetic approach to preparing an integrated materials/cells/signaling construct that orchestrates a univocal result. For this aim, several proposals targeted at muscle regeneration have already been presented, focusing on (i) the materials, synthetic and natural ones, and their combinations [ 5 , 6 , 9 ], (ii) the fabrication techniques to evaluate their role on scaffold morphology and properties [ 10 , 11 , 12 ], (iii) the surface functionalization [ 13 ], (iv) the cells to be used, stem cells or already committed [ 6 , 10 ], (v) the addition of different nanomaterials to deal with constructs responsive to electrical, magnetic and photothermal stimulation [ 14 ] and (vi) the methods to specifically induce vascularization, innervation and contractility [ 10 , 13 ]. More than interesting and promising findings have been reported; however, the proper cellular microenvironment to bioengineer the SM construct has not, to date, been found, and there is still a clinical need to introduce new strategies that can facilitate safe and large muscle tissue repair and regeneration [ 13 ].…”
Section: Introduction: the Current Scenariomentioning
confidence: 99%